So you not only know<span> how fast it is going, but where it is going.</span>
The average velocity of the whole journey will be total distance covered divided by the total time. It will be approximately equal to 8 m/s. The right answer is option B
<h2>VELOCITY</h2>
Velocity is the distance travelled in a specific direction. While the average velocity of the whole journey will be total distance covered divided by the total time
When driving a Toyota avensis car along a straight road for 16.5km at
50km/h,
The velocity = 50 km/h
Distance = 16.5 km
Use the speed formula to calculate time.
Speed = distance / time
Time = distance / speed
Time = 16.5 / 50
Time = 0.33 s
If over the next 20min, you walked another 2.5km further along the road for a petrol station, Then,
average velocity = Total distance covered divided by total time taken.
Where
The time t = 20/60 = 0.333 h
Total time = 0.33 + 0.3333
Total time = 0.6633333
Total distance = 16.5 + 2.5
Total distance = 19 km
Average velocity = 19 / 0.66333
Average Velocity = 28.64 km/h
Now convert Km/h to m/s
(28.6432 x 1000) / 3600
286432 / 3600
7.956m/s
Therefore, the average velocity of the whole journey from beginning of the drive to the arrival at the filling station will be approximately 8 m/s
Learn more about velocity here: brainly.com/question/6504879
As well as the electric and magnetic fields being perpendicular to eachother, a wave moves perpendicularly to both
Answer:
d²x/dt² = - 4dx/dt - 4x is the required differential equation.
Explanation:
Since the spring force F = kx where k is the spring constant and x its extension = 2.45 equals the weight of the 4 kg mass,
F = mg
kx = mg
k = mg/x
= 4 kg × 9.8 m/s²/2.45 m
= 39.2 kgm/s²/2.45 m
= 16 N/m
Now the drag force f = 16v where v is the velocity of the mass.
We now write an equation of motion for the forces on the mass. So,
F + f = ma (since both the drag force and spring force are in the same direction)where a = the acceleration of the mass
-kx - 16v = 4a
-16x - 16v = 4a
16x + 16v = -4a
4x + 4v = -a where v = dx/dt and a = d²x/dt²
4x + 4dx/dt = -d²x/dt²
d²x/dt² = - 4dx/dt - 4x which is the required differential equation